2009
DOI: 10.5051/jkape.2009.39.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of statistical methods in the Journal of Korean Academy of Periodontology published from 2000 to 2006

Abstract: Purpose: This article is purposed to present the correct statistic method by pointing out the statistical errors after analyzing the method of articles that were published in Korean Academy Journal of Periodontology and made statistic processes in them. Methods: 488 science papers which being put in Korean Academy Journal of Periodontology published from 2000 to 2006 was divided according to year. Results: In the 308 articles that applied statistic methods, 59 articles (50.0%), the largest portion of all, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results of this study showed a trend of increasing application of statistical methods and increasing use of nonparametric methods in recent periodontal studies in Korea. The percentage of studies using statistics published in JPIS between 2010 and 2014 was 64.4%, which is higher than the 19.3%, 49.0%, and 63.1% in periodontal studies published in Korea during the periods of 1973-1989, 1990-1999, and 2000-2006, respectively [ 9 , 10 ]. Therefore, there was a trend towards increasing use of statistical applications.…”
Section: Discussionmentioning
confidence: 95%
“…The results of this study showed a trend of increasing application of statistical methods and increasing use of nonparametric methods in recent periodontal studies in Korea. The percentage of studies using statistics published in JPIS between 2010 and 2014 was 64.4%, which is higher than the 19.3%, 49.0%, and 63.1% in periodontal studies published in Korea during the periods of 1973-1989, 1990-1999, and 2000-2006, respectively [ 9 , 10 ]. Therefore, there was a trend towards increasing use of statistical applications.…”
Section: Discussionmentioning
confidence: 95%